2010
DOI: 10.5047/eps.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of a muon radiographic imaging electronic board system for a stable solar power operation

Abstract: Cosmic-ray muon radiography is a method that is used to study the internal structure of volcanoes. We have developed a muon radiographic imaging board with a power consumption low enough to be powered by a small solar power system. The imaging board generates an angular distribution of the muons. Used for realtime reading, the method may facilitate the prediction of eruptions. For real-time observations, the Ethernet is employed, and the board works as a web server for a remote operation. The angular distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Each MOS consisted of a muon tracker (consisting of 2 segmented detectors as shown in Fig. 3b), high voltage (HV) supply, field-programmable-gate-array (FPGA)-based electronics for signal processing29, and data acquisition (DAQ) personal computer (PC). Each scintillation detector consisted of a plastic scintillator bar (ELJEN EJ-200), photomultiplier tube (PMT; Hamamatsu R7724), and acryl light guide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each MOS consisted of a muon tracker (consisting of 2 segmented detectors as shown in Fig. 3b), high voltage (HV) supply, field-programmable-gate-array (FPGA)-based electronics for signal processing29, and data acquisition (DAQ) personal computer (PC). Each scintillation detector consisted of a plastic scintillator bar (ELJEN EJ-200), photomultiplier tube (PMT; Hamamatsu R7724), and acryl light guide.…”
Section: Resultsmentioning
confidence: 99%
“…This angular resolution corresponded to a spatial resolution of ~90 m at the peak of the 1994 spine. 28 signal outputs from each muon tracker were fed to the electronics to generate a histogram of the number of muon events as a function of azimuth and elevation angles29. The histogram was stored in a flash memory drive associated with the FPGA so that the DAQ PC could access the FPGA and download the data every minute.…”
Section: Resultsmentioning
confidence: 99%
“…Electromagnetic (EM) showers and multi-muon events are rejected by discarding events when more than one signal from the same layer (detector plane) coincides in a time gate of 100 ns (multiplicity cut). The prior experiments on muon imaging with FPGA-based (field programmable gate array) Muon Readout Module, developed by Uchida et al (2010) demonstrated the very low readout noise, high-speed event counting, and accurate timing of the acquisition frames. The readout frames can be as short as one microsecond.…”
Section: Methodsmentioning
confidence: 99%
“…Uchida et al (2009Uchida et al ( , 2010 developed MURG08 for non-particle physicist users. In this system, in order to increase the availability, the tracking analysis algorithm is also incorporated into FPGA so that users can monitor the single counting rate of each channel as well as the 2-D histogram of the muon counts as a function of azimuth and elevation angle only by accessing the web browser equipped on the electronics board via the internet.…”
Section: Test Measurement With the Multi-psd Systemmentioning
confidence: 99%